The notion of "home" in Czech translations of the R. M. Rilke's poetry book Larenopfer - Gutiérrez Rubio, Enrique (Bohemica Olomucensia, 2014)
In this article is presented an analysis of the Czech word "domov" and its counterparts in German (Heim, Heimat), English (home), and Spanish (hogar). It is inferred that there are two main semantics regarding the concept "domov" in these four languages - a first one related to a more material and physical conception (domov-místnost) and a second one with more emotional and even philosophical connotations (domov-místo).In a second part, these two kinds of conceptions of "domov" will be examined in the work of the Prague German-language poet Rilke, and more specifically in Larenopfer.